Tooth replantation after keeping the avulsed tooth in oral environment: case report of a 3-year follow-up - Sonoda, Celso Koogi [UNESP]; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sottovia, Andre Dotto [UNESP]; Okamoto, Tetuo [UNESP] (Wiley-Blackwell, 2008)
Clinical practice has shown that most avulsed teeth are replanted after an extra-alveolar time that compromises the prognosis of replantation. In cases of delayed replantation, the use of adequate media for storage and transportation of the avulsed teeth may improve this prognosis considerably. Difficulties inherent to accidental dental avulsion include the lack of immediate access to ideal storage media, which accentuates the importance of saliva as a viable and readily available option. The authors report the case of an accidentally avulsed permanent maxillary central incisor that was kept into the patient's oral cavity from the moment of trauma until its replantation, 90 min later. Three years of follow-up revealed absence of root resorption, ankylosis or abnormal mobility, which demonstrates the feasibility of keeping avulsed teeth in saliva, at least when more indicated storage media are not available immediately.